Language learning strategies applied by Arabic learners: a case-study at Institute of Education, International Islamic University Malaysia (IIUM) - Mamat , Arifin; Sideh, Ibrohem (International Organisation of Scientific Research (IOSR), 2013)
Language learning strategies (LLS) play an important role in a second/foreign language acquisition, as they promote and facilitate language learning. This study aims to investigate LLS used by students in learning the Arabic language. The respondents of the study were all final year students at the Institute of Education, the International Islamic University of Malaysia (IIUM). Strategy Inventory for Language Learning (SILL) developed by Oxford (1990) was used to gather the data for the study. While, a simple descriptive statistical analysis was employed to provide meanings to the data. It includes frequency distribution, percentages, means, standard deviation and range of scores for the data set. The study reveals that students were familiar with entire six LLS categories namely; memory, cognitive, compensation, metacognitive, affective, and social strategies, with a medium frequency level use for overall strategies (M = 3.49). Among these six strategies, the most frequently used from the top was metacognitive, compensation, social, memory, cognitive, and affective strategies.